Exploration of Feasible Immune Biomarkers for Immune Checkpoint Inhibitors in Head and Neck Squamous Cell Carcinoma Treatment in Real World Clinical Practice - Wang, Hui-Ching (Int J Mol Sci, 2020)
Recurrent locally advanced or metastatic head and neck squamous cell carcinoma (HNSCC) is associated with dismal prognosis because of its highly invasive behavior and resistance to conventional intensive chemotherapy. The combination of targeted therapy and conventional chemotherapy has significantly improved clinical outcomes. In recent years, the development of immunotherapies, such as immune checkpoint inhibitors (ICIs), has further increased treatment responses and prolonged survival. However, the limited response rate, risk of immunotherapy-related adverse effects and high cost of immunotherapy make the identification of predictive markers to optimize treatment efficacy a critical issue. Biomarkers are biological molecules that have been widely utilized to predict treatment response to certain treatments and clinical outcomes or to detect disease. An ideal biomarker should exhibit good predictive ability, which can guide healthcare professionals to achieve optimal treatment goals and bring clinical benefit to patients. In this review, we summarized the results of recent and important studies focused on HNSCC ICI immunotherapy and discussed potential biomarkers including their strengths and limitations, aiming to gain more insight into HNSCC immunotherapy in real world clinical practice.